Karakteristik Velva Labu Kuning LA3 (Cucurbita moschata) Dari Campuran Labu Kuning-Air Dan Jenis Bahan Penstabil - Fauzi, Mukhammad; Giyarto, Giyarto; Rusdianto, Andrew S; Jannah, Sulihati (AGRITEKNO: Jurnal Teknologi Pertanian, 2024)
Diversified fruit processing technology offers an alternative to improve undesirable flavors, adding value and extending shelf life. The LA3 pumpkin (Cucurbita moschata) has a pleasant taste and significant potential for processing into fruit velva. Yellow pumpkin velva is known for its smooth texture and resistance to melting. The choice of stabilizer significantly affects its consistency. This research aims to determine the most suitable stabilizer for producing LA3 pumpkin velva, with desirable melting resistance and favorable panelist preferences. A Completely Randomized Design (CRD)was employed, with factor A being the ratio of pumpkin: water (200 g: 40 mL; 200 g: 80 mL; 200 g: 120 mL; and 200 g: 160 mL), and factor B being the type of stabilizer (CMC and gum arabic). The objective was to determine the optimal formulation and stabilizer for LA3 pumpkin velva production. The research results showed that the best treatment LA3 pumpkin velva involved the ratio of 200 g pumpkin to 80 mL water with the CMC stabilizer, yielding an overrun of 21.23%, a melting speed of 18.57%, a lightness value (L*) of 46.09, and a β carotene content of 0.46 mg/100g of material. The organoleptic evaluation showed preference scores for taste at 4.08, color at 4.16, aroma at 4.16, texture at 4.16, and overall acceptance at 4.20.